Implementation of Vygotsky's Theory of Social Constructivism in Learning Pancasila Education in Elementary Schools As Strengthening Cooperation Attitudes - Dewi, Ressi Kartika; Yusuf, Munawir; Subagya, Subagya (Universitas Pendidikan Mandalika, 2025)
This study aims to reveal the implementation of Vygotsky's theory of social constructivism in learning Pancasila education to strengthen students' cooperative attitudes. This study used a phenomenological method with a qualitative approach. The subjects in this study were teachers who teach Pancasila education subjects and grade III students at Gondangmanis State Elementary School, Karanganyar Regency, Central Java Province. The data collection technique was carried out by observation and interviews, which were then checked for validity of the data using triangulation techniques and sources, the data analysis used was interactive analysis. The results of the study showed that the theory of social constructivism was relevant to strengthening the attitude of cooperation in Gondangmanis State Elementary School in the learning of Pancasila Education. Gondangmanis State Elementary School still tends to be selective in choosing their group mates, but after the teacher implements Vygotsky's theory of social constructivism through Pancasila Education learning, students easily blend in with each side regardless of differences. It can happen because teachers divide groups randomly regardless of the differences in students' backgrounds after being divided, students are required to cooperate in the group to complete the tasks given by the teacher. Through this process, the attitude of cooperation of students can be built well because they are used to working with each student regardless of differences in background, both differences in religion, ethnicity, and area of residence.